Protective effects of intraperitoneal vitamin C, aprotinin and melatonin administration on retinal edema during experimental uveitis in the guinea pig - Kükner, AS; Kükner, A; Naziroglu, M; Çolakoglu, N; Çelebi, S; Yilmaz, T; Aydemir, O (Wiley, 2004)
A considerable amount of clinical and experimental evidence exists suggesting the involvement of reactive oxygen substances (ROS) in the actiology of uveitis. The activated phagocytic system of polymorphonuclear leucocytes in uveitis is involved in the generation of ROS. In addition to their direct free radical scavenging action, aprotinin, melatonin and vitamin C are known to protect against oedema formation and can preserve plasma membrane fluidity and free radical production. Histological changes in the retina that occur during uveitis are not well explained. The purpose of this study was to determine whether vitamin C, aprotinin and melatonin can protect the retina from damage accompanying experimental uveitis (EU). Thirty adult male guinea pigs were divided into five groups of six animals each. The first group was used as control. The right eyes of groups 2, 3, 4 and 5 received an intravitreal injection of bovine serum albumin for induction of experimental uveitis. At the same time and also on the consecutive third day, groups 3, 4 and 5 received intraperitoneal injections of vitamin C (ascorbic acid, 100 mg kg(-1) body wt), aprotinin (20 000 mg kg(-1) body wt) and melatonin (10 mg kg(-1) body wt), respectively. The animals were killed on the sixth day. The average thickness of the retina and inner plexiform layer for each eye was measured in sagittal section near the optic nerve and expressed in microns. The thickness of the retina and inner plexiform layer in the control group was significantly (p < 0.01) lower than in the group EU as compared with the group EU plus vitamin C, group EU plus aprotinin, group EU plus melatonin (p < 0.05). The thicknesses of the retina and inner plexiform layer in group EU plus vitamin C, group EU plus aprotinin and group EU plus melatonin were significantly (p < 0 01) lower than that in the group EU. The difference in thickness of the retina and inner plexiform layer among the groups 3, 4 and 5 was not significant (p > 0.05). In conclusion, this study demonstrated that oedematous effects of EU on the retina were reduced by the administration of intraperitoneal vitamin C, aprotinin and melatonin, i.e. these antioxidants had significant protective effects on the retina of guinea pigs against oedematous damage in EU. However, the reductive effect of vitamin C on EU was greater than that of aprotinin and melatonin. The intraperitoneal vitamin C, aprotinin and melatonin supplementations may strengthen the antioxidant defence system because of decreased ROS, and these agents may play a role in treating uveitis. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: EU; experimental uveitis; BSA; bovine serum albumin; ROS; reactive oxygen substances; PMN; polymorphonuclear leucocytes